Highly active antiretroviral therapy and changing spectrum of liver diseases in HIV infected patients - Joshi, Kavita S.; Shriwastav, Rohit R. (International Journal of Research in Medical Sciences, 2017)
Background: HIV is now considered as chronic disease than a fatal disease. HIV infected individual is having normal life expectancy post highly active antiretroviral therapy (HAART) era. Liver disease is the major cause of morbidity and mortality in HIV infected patients. The objective was to study the prevalence, clinical profile of various liver diseases in HIV infected individuals on HAART and also to study aetiologies of liver involvement in HIV patients. Methods: It was a cross sectional observational study conducted from August 2014 to July 2015. 102 HIV positive individuals on HAART with liver involvement were included. Detailed history and clinical examination were noted. Baseline investigations (Hb, CBC, blood sugars, liver function tests, electrocardiogram, chest X-ray, urine routine and microscopy), special investigations (HBsAg, anti-HCV, CD4 count, ultrasonography, CT scan, ascitic fluid examination) were performed. The data was analyzed using descriptive statistics. Results are expressed as percentage. Results: Out of the total 102 patients, 78 (76.5%) patients were male and 24 (23.5%) patients were female. The maximum number of patients belonged to the age group 41-50 years (38.2%). Hepatitis B (30.8%) was most common liver disease in males and AKT induced hepatitis (41.7%) most common liver disease in females. The most presenting symptom of patients with liver involvement in HIV was weakness and fatigue 82 (80.39%). The most common clinical sign was icterus 39 (38.23%), sonography finding was coarse echotexture of liver (46.07%) suggestive of cirrhosis. Conclusions: Although hepatitis B and alcoholic liver disease are major causes of liver diseases in HIV patients in India, incidence of drug related hepato toxicities are increasing.